Massagem com aromaterapia e sua eficiência para o usuário em internação psiquiátrica - Domingos, Thiago da Silva [UNESP] (2013)
Psychiatric nursing and mental health care have followed the numerous changes that have taken place in medicine and in the social, historical and cultural realms. Hence, care provision to patients with mental disorders has been outlined in light of the Psychiatric Reform and Psychosocial Rehabilitation based on precepts such as humanization, resocialization and reintegration of such users into society, thus causing abrupt changes in the micro policies of work, in health care team members, in patients’ relatives and in care provision devices in the mental health care network. With the purpose to pluralize care practices in the Unified Public Health System (SUS), complementary practices have been available in Brazil since 1970, although in a non-systematized fashion. In 2006, the Health Department (HD) published the National Policies for Integrative and Complementary Health Care Practices (Política Nacional de Práticas Integrativas e Complementares em Saúde [PNPIC]), thus ensuring to professionals the application of such techniques. Among such practices, aromatherapy is mentioned, and its use has presently increased in Nursing as one of the main professional classes representing that therapy type. It consists in the use of essential oils by means of inhalation, dermal application and smelling, with the purpose of prevention and treatment. Therefore, this study aims at analyzing the efficacy of massage with aromatherapy on the anxiety of patients hospitalized in a psychiatric hospitalization unit, using, as parameters, a nationally and internationally validated anxiety scale (STAI), the measurement of heart and respiratory rates and users’ experience in relation to that practice. It is a quanti-qualitative study with a non-controlled clinical-trial design applied in the psychiatric hospitalization unit of the Marilia School of Medicine University Hospital (FAMEMA). The population in the study consisted of fifty subjects ...